EVALUASI KEGIATAN PENYULUHAN PERTANIAN DALAM UPAYA PENINGKATAN PRODUKTIVITAS PADI DI DESA BENDOSARI KABUPATEN SUKOHARJO: EVALUASI KEGIATAN PENYULUHAN PERTANIAN DALAM UPAYA PENINGKATAN PRODUKTIVITAS PADI DI DESA BENDOSARI KABUPATEN SUKOHARJO - Fifit Rahma; Annisa Khoiriyah; Sukadi (Program Studi Pendidikan Masyarakat, Universitas Mulawarman, 2026)
Abstract Rice productivity in Bendosari Village, Bendosari District, Sukoharjo Regency has not yet reached its optimal potential amounting to 31.10 million tons, despite the regular implementation of agricultural extension activities (BPS, 2024). This condition indicates the need to evaluate the implementation of agricultural extension to determine its contribution to improving rice productivity. This study aimed to analyze the implementation of agricultural extension, including extension materials, extension methods, extension media, and extension resources, and to examine their influence on rice productivity. The research employed a quantitative approach using descriptive and correlational research designs. The study population consisted of 82 rice farmers from two farmer groups, with a sample of 30 respondents selected through purposive sampling. Data were collected using questionnaires, structured interviews, and documentation, and were analyzed using descriptive statistics and multiple linear regression with the assistance of SPSS software. The results showed that the implementation of agricultural extension and rice productivity were both categorized as high, with an average productivity score of 82.38%. Multiple linear regression analysis revealed that extension materials, extension methods, and extension resources had a positive and significant effect on rice productivity, whereas extension media had no significant effect. Simultaneously, the four variables explained 77.7% of the variation in rice productivity, with extension resources identified as the most influential factor affecting rice productivity.